Adaptation to Rainfall Variability by Smallholder Farmers in Kwale County: A Case Study of Samburu and Tsimba Locations - Richard , Ochieng‘; Francis , Wegulo; John , Mironga; Edward , Masakha; Ednah , Koskei (African Journal of Education,Science and Technology (AJEST), 2015)
Rainfall received in Kwale County is highly variable negatively affecting agricultural production. Due to these variations, smallholder farmers in Kwale County have attempted to implement various adaptation mechanisms to help them cope. These include: sending children to school to enable them avail remittances when they get employed, seeking for seasonal jobs, work for food, embracing non-farm economic activities, planting of early maturing and drought tolerant crops, shifting from crop to livestock production or change in herd composition among others. These approaches have met a number of challenges such as: lack of improved seeds and information on weather incidences, inadequate capital to practice modern methods of farming, limited market to dispose of livestock during drought, frequent attack by pests and diseases. This study was conducted in Kwale County using survey research design and sought to determine effects rainfall variability and adaptation mechanisms used by the smallholder farmers in Kwale County. A sample of 272 households was picked through stratified and systematic sampling technique from Samburu and Tsimba Locations. Data was collected by use of pretested questionnaire from the sampled respondents and analyzed using Microsoft Office Excel and SPSS softwares. The study made the following recommendations to help improve the farmers‟ ability to adapt to rainfall variability: the number of functional meteorological stations in the County should be increased; the poor smallholder farmers should be empowered to fully implement rainwater harvesting technique, diversify and engage in both farm and non-farm economic activities that will ensure that the risks associated with rainfall variability are spread; the smallholder farmers should be supplied with adequate, high yielding and drought tolerant seed and encouraged to implement agroforestry programmes.